Decreased synaptic vesicle glycoprotein 2A binding in a rodent model of familial Alzheimer's disease detected by [18F]SDM-16 - Zheng, Chao; Toyonaga, Takuya; Chen, Baosheng; Nicholson, LaShae; Mennie, William; Liu, Michael; Spurrier, Joshua; Deluca, Kristin; Strittmatter, Stephen M.; Carson, Richard E.; Huang, Yiyun; Cai, Zhengxin (Frontiers in Neurology, 2023)
Introduction Synapse loss is one of the hallmarks of Alzheimer's disease (AD) and is associated with cognitive decline. In this study, we tested [18F]SDM-16, a novel metabolically stable SV2A PET imaging probe, in the transgenic APPswe/PS1dE9 (APP/PS1) mouse model of AD and age-matched wild-type (WT) mice at 12 months of age. Methods Based on previous preclinical PET imaging studies using [11C]UCB-J and [18F]SynVesT-1 in the same strain animals, we used the simplified reference tissue model (SRTM), with brain stem as the pseudo reference region to calculate distribution volume ratios (DVRs). Results To simplify and streamline the quantitative analysis, we compared the standardized uptake value ratios (SUVRs) from different imaging windows to DVRs and found that the averaged SUVRs from 60–90 min post-injection (p.i.) are most consistent with the DVRs. Thus, we used averaged SUVRs from 60–90 min for group comparisons and found statistically significant differences in the tracer uptake in different brain regions, e.g., hippocampus (p = 0.001), striatum (p = 0.002), thalamus (p = 0.003), and cingulate cortex (p = 0.0003). Conclusions In conclusion, [18F]SDM-16 was used to detect decreased SV2A levels in the brain of APP/PS1 AD mouse model at one year old. Our data suggest that [18F]SDM-16 has similar statistical power in detecting the synapse loss in APP/PS1 mice as [11C]UCB-J and [18F]SynVesT-1, albeit later imaging window (60–90 min p.i.) is needed when SUVR is used as a surrogate for DVR for [18F]SDM-16 due to its slower brain kinetics.